Pengaruh Keluarga dan Teman Sebaya terhadap Pembentukan Identitas Sosial Individu - Eka Faidah Khasanah; Musripah (Universitas Islam Raden Rahmat Malang, 2025)
The purpose of this study is to understand the extent to which family and peers can shape social behavior and individual identity. This study uses a qualitative approach with library research, involving a review of readings relevant to the topic under discussion. Data were collected from sources such as books, scientific journals found on Google Scholar, and other digital libraries. The following conclusion can be drawn based on the explanation provided: peers and family are the main determinants in the formation of individual identity. Peers are social groups consisting of people who are similar to each other in terms of age, education, or social status, whereas family is the primary institution responsible for raising individuals, incorporating all social norms and ethics. It is hoped that this research will be used as a guide in formulating inclusive and socio-culturally aware educational policies.